The Influence of Religiosity, Zakat Literacy and Trust on Muzakki's Interest in Paying Professional Zakat at Baznas Jakarta Province - Erna Kustyarini; Efendi Sugianto; Ilham Rahim; Sa'diyah MA; Muhammad Umar Kelibia (CV. Ulil Albab Corp, 2024)
This study aims to understand the factors that influence individual interest as muzakki in paying professional zakat through BAZNAS Jakarta Province. The method used is a field study with a quantitative approach. The sample consisted of 97 muzakki who had or had never paid zakat through BAZNAS Jakarta Province. Primary data were collected through questionnaires distributed to respondents. Regression analysis shows that zakat literacy and belief have a positive and significant influence on individual interest as muzakki to pay professional zakat to BAZNAS Jakarta Province, while religiosity has no effect on muzakki interest in paying professional zakat at BAZNAS Jakarta province.